Analysis of pedagogical and cultural situations from the vantage point of discourse analysis - Murillo-Murgueítio, Antonio José (Colombian Applied Linguistics Journal, 2003)
This paper encompasses analyses of pedagogical and cultural situations from the perspective of some of the authors studied in our discourse analysis class. Cultural authenticity and cultural stereotypes are dealt with stemming from real issues and mirroring them through the lens of Kramsch´s (1998) insights. McCarthy (1994) is referred to when a curricular principle, the familiar to unfamiliar principle is considered as a pedagogical approach in ESL teaching.